Pengaruh kecerdasan intelektual, emosional dan spiritual terhadap hasil belajar matematika siswa 8 SMP di Kota Tangerang - Kusnandar (Universitas Tangerang Raya, 2024)
In this article the author discusses the influence of intellectual, emotional and spiritual intelligence on the mathematics learning outcomes of 8 junior high school students in Tangerang city. This study aims to determine the effect of intellectual, emotional and spiritual intelligence on math learning outcomes. The technique used in this research is survey method with multiple regression analysis research design which is selected and adjusted to the research hypothesis. The research was conducted in junior high schools in Tangerang city consisting of 3 schools, namely SMPN 3 with 84 students, SMPN 4 with 90 students and SMPN 23 with 89 students. Based on the results of the study, the t-count value is 0.513 < t-table 1.980, then H0 is accepted, it is concluded that there is no effect of academic potential, emotional intelligence, and spiritual intelligence of students together on mathematics learning achievement.